The Contribution of The Maju Tapian Nauli Foundation (Matauli) to Education Development in Central Tapanuli Regency - Suherlan, Ano; Asari, Hasan; Arsyad, Junaidi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study analyses the MATAULI Foundation's role in enhancing educational access and quality in Tapanuli Tengah Regency, a region characterised by geographical and socio-economic constraints. Educational inequities in marginalised regions of Indonesia persist as a significant concern, requiring the involvement of community-based institutions to address them. This study aims to assess the role and contributions of the MATAULI Foundation, namely via MATAULI High School, which emphasises diversity, character education, and academic success. The study utilises a qualitative methodology using a case study framework, incorporating in-depth interviews, observations, and document analysis. The findings indicate that SMA MATAULI employs a clear meritocratic selection procedure, offers scholarships and dormitory accommodations for disadvantaged students, and provides high-quality education complemented with character development initiatives. Students from diverse coastal and rural regions have attained national acclaim, and alumni have gained admission to esteemed universities both nationally and globally. The amalgamation of ethical principles with educational benchmarks yields graduates who are anchored in local culture while remaining globally competitive. In summary, community-based educational institutions, when administered with openness and a definitive goal, can mitigate educational inequalities and enhance social mobility. The MATAULI approach can be duplicated in other locations encountering analogous obstacles, thus exemplifying the transformative potential of locally based education in Indonesia.